2015
DOI: 10.1118/1.4927257
|View full text |Cite
|
Sign up to set email alerts
|

Practical dose point‐based methods to characterize dose distribution in a stationary elliptical body phantom for a cone‐beam C‐arm CT system

Abstract: Purpose: To propose new dose point measurement-based metrics to characterize the dose distributions and the mean dose from a single partial rotation of an automatic exposure control-enabled, C-armbased, wide cone angle computed tomography system over a stationary, large, body-shaped phantom. Methods: A small 0.6 cm 3 ion chamber (IC) was used to measure the radiation dose in an elliptical body-shaped phantom made of tissue-equivalent material. The IC was placed at 23 well-distributed holes in the central and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[92][93][94][95][96] Choi et al have recently reported that a proximity-based weighting method and a 2D surface fitting method can accurately estimate the planar average dose in an elliptical phantom using as few as 5 point dose measurements. 91 The measurement of f (0) in a single 16-cm CTDI phantom can also be limited by the fact that the longitudinal extent of a single phantom is not sufficient to capture the entire contribution of dose from scatter at the edges of the longitudinal extent of the beam, especially if the longitudinal extent of the beam at isocenter is greater than the extent of the phantom. In the case of the beam exceeding the longitudinal extent of the measurement phantom, the beam may be collimated to a limited range for the C-arm CBCT acquisition, or two or more phantoms may be stacked in series to create a longer phantom to capture the entire contribution to the central plane dose from scatter (Figure 19a).…”
Section: 32mentioning
confidence: 99%
See 2 more Smart Citations
“…[92][93][94][95][96] Choi et al have recently reported that a proximity-based weighting method and a 2D surface fitting method can accurately estimate the planar average dose in an elliptical phantom using as few as 5 point dose measurements. 91 The measurement of f (0) in a single 16-cm CTDI phantom can also be limited by the fact that the longitudinal extent of a single phantom is not sufficient to capture the entire contribution of dose from scatter at the edges of the longitudinal extent of the beam, especially if the longitudinal extent of the beam at isocenter is greater than the extent of the phantom. In the case of the beam exceeding the longitudinal extent of the measurement phantom, the beam may be collimated to a limited range for the C-arm CBCT acquisition, or two or more phantoms may be stacked in series to create a longer phantom to capture the entire contribution to the central plane dose from scatter (Figure 19a).…”
Section: 32mentioning
confidence: 99%
“…Following the conventions introduced in the AAPM Report 111, 88 the dose profile along the z‐axis of a CT acquisition is ffalse(zfalse)$f( z )$, and a measurement of the dose at the center of the scan range is defined as f (0). The distribution of dose in a plane for a C‐arm CBCT acquisition is not radially or angularly symmetric 91–95 . Accordingly, measurements of the dose profile or the dose at the central extent of the scan range must be acquired at different angular positions and may be defined as fposition(z)${f}_{position}( z )$ or fposition(0)${f}_{position}( 0 )$ where the position is the angular position of the placement of the dosimeter in the measurement phantom, with 0 degrees defined to be along the positive y‐axis of a cross‐sectional view of the phantom and 90 degrees is along the positive x‐axis, and so on.…”
Section: C‐arm Cbct Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Fig. 4 , during the AEC scan the tube outputs (i.e., the tube voltage and tube current-time product per projection) were modulated by the AEC system as a function of the projection number [ 28 ], [ 29 ]. While the gantry of the C-arm CT system rotated around the two knees together, the AEC elevated the tube outputs along the lateral direction at the beginning and end of the scan, and reduced the output in the anterior-posterior direction where the legs do not overlap.…”
Section: Experimental Evaluationmentioning
confidence: 99%
“…J.H. Choi et al propose new dose point measurement-based method to characterize the dose distributions and the mean dose from a single partial rotation of a CBCT system over a stationary, large, body-shaped phantom validated by a Geant4 simulation [112].…”
Section: Rq2: Which Are the Most Common Cbct Applications That Use Geant4 Simulations To Estimate The Dose And How Have They Changed Overmentioning
confidence: 99%